The Oxford handbook of process philosophy and organization studies - Helin, Jenny; Hernes, Tor; Hjorth, Daniel; Holt, Robin, 1966- (Oxford : Oxford University Press, 2014)
Process approaches to organization studies focus on flow, activities, and evolution, understanding organizations and organizing as processes in the making. They stand in contrast to positivist approaches that see organizations and phenomena as fixed, static, and measurable. Process approaches draw on a range of ideas and philosophies. The handbook examines 34 philosophers and social theorists, both those commonly linked to process thinking, such as Whitehead, Bergson and James, and those that are not as often addressed from a process perspective such as Dilthey and Tarde. Each chapter addresses the background and context of this thinker, their work (with a focus on the processual elements), and the potential contribution to organization and management research.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on September 30, 2014).
Keywords: Organization -- Philosophy; Management -- Philosophy; Process philosophy